Reduction of Fe and Ni in Fe-Ni-O systems (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
The reduction behaviors of Fe-Ni-O compounds/systems (NiO, Fe2O3, NiFe2O4, Fe2O3 + NiO and Fe2O3 + Ni) were studied using H2 and activated carbon as reducing agents, and the mechanism of NiFe2O4 reduction was analyzed. With H2 as reductant, these systems showed lower starting reaction temperatures and lower reaction rates. The reaction rate differences among these samples were small compared to those using C. With C as reductant, the reduction of the Fe2O3 + NiO system was much more facile compared to NiFe2O4, Fe2O3 + Ni, and pure Fe2O3.  In both cases, NiFe2O4 appeared to be more difficult to reduce, as it required a higher starting temperature and exhibited a lower reaction rate and lower final reduction degree. Additionally, the data suggested that with increasing temperature, the products for the reduction of NiFe2O4 appeared in the order NiFe2O4 → Fe3O4 + NiO → Fe3O4 + Ni → FeO + FexNiy → FexNiy + Fe (FemCn). Based on this data, kinetic information about the H2 reduction for the five compounds/systems, such as apparent activation energy and reaction mechanism, was obtained and discussed.
Keywords: Fe-Ni-O system; H2; activated carbon; reduction behavior; kinetic